1993
DOI: 10.1103/physrevlett.71.4226
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi-liquid behavior in quantum critical systems

Abstract: The problem of an electron gas interacting via exchanging transverse gauge bosons is studied using the renormalization group method. The long wavelength behavior of the gauge field is shown to be in the Gaussian universality class with a dynamical exponent z = 3 in dimensions D ≥ 2. This implies that the gauge coupling constant is exactly marginal. Scattering of the electrons by the gauge mode leads to non-Fermi liquid behavior in D ≤ 3. The asymptotic electron and gauge Green's functions, interaction vertex, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
102
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 24 publications
12
102
0
Order By: Relevance
“…This is in agreement with previous work [7,8,11], and points to a possible non-Fermi behavior in d ≤ 3, as previously observed in the context of gauge theories [11] and recently noted in the context of a ferromagnet [12]. To summarize, we introduced an RG scheme in the spirit of the Shankar approach [9], which allows to treat the fermion and the boson degrees of freedom in the spinfermion models on an equal footing.…”
supporting
confidence: 73%
“…This is in agreement with previous work [7,8,11], and points to a possible non-Fermi behavior in d ≤ 3, as previously observed in the context of gauge theories [11] and recently noted in the context of a ferromagnet [12]. To summarize, we introduced an RG scheme in the spirit of the Shankar approach [9], which allows to treat the fermion and the boson degrees of freedom in the spinfermion models on an equal footing.…”
supporting
confidence: 73%
“…It is known that in this case the system shows non-Fermi-liquid behavior for Dр3, manifested in properties like the specific heat or anomalous electron field dimensions. [11][12][13] In the present work, we address the applicability of the notion of Fermi-liquid fixed point to two-dimensional systems with unscreened Coulomb interaction. The absence of screening requires the vanishing of the density of states at the Fermi level.…”
Section: ͓S0163-1829͑99͒50204-x͔mentioning
confidence: 99%
“…There have been several studies of the two-particle correlation functions which concentrated on the non-renormalization of the gauge field propagator [11][12][13][14]16]. Recently three of us with Furusaki have examined several gauge invariant two-particle correlation functions for all ratios of ω and q [17].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the gauge field fluctuations give rise to a singular contribution to the self-energy in the oneparticle Green's function of the composite fermions [5,8]. Later various kinds of methods were used to go beyond the perturbation theory [9][10][11][12][13][14][15][16], which were motivated by the fact that the singular self-energy correction leads to a divergent effective mass of the composite fermions [5]. If one applied this divergent effective mass to the Shubnikov-de Haas effect near ν = 1/2, one would find that the gap ∆ p of ν = p/(2p ± 1) FQH state goes down faster than 1/p as p → ∞:…”
Section: Introductionmentioning
confidence: 99%